2018
DOI: 10.3390/ijms19082455
|View full text |Cite
|
Sign up to set email alerts
|

The Dead Can Nurture: Novel Insights into the Function of Dead Organs Enclosing Embryos

Abstract: Plants have evolved a variety of dispersal units whereby the embryo is enclosed by various dead protective layers derived from maternal organs of the reproductive system including seed coats (integuments), pericarps (ovary wall, e.g., indehiscent dry fruits) as well as floral bracts (e.g., glumes) in grasses. Commonly, dead organs enclosing embryos (DOEEs) are assumed to provide a physical shield for embryo protection and means for dispersal in the ecosystem. In this review article, we highlight recent studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Recent studies have demonstrated that Reactive Oxygen Species (ROS) have key roles in the release of seed dormancy, as well as in protection from pathogens [70][71][72]. Thioredoxins were identified to promote seed germination [73]. Peroxidases (EC 1.11.1.7) are also implicated in lignin/suberin formation during the polymerization of monolignols synthetized in the final steps of the phenylpropanoid pathway [74].…”
Section: Genetic Basis Of Seed Dormancy Release In Legumesmentioning
confidence: 99%
“…Recent studies have demonstrated that Reactive Oxygen Species (ROS) have key roles in the release of seed dormancy, as well as in protection from pathogens [70][71][72]. Thioredoxins were identified to promote seed germination [73]. Peroxidases (EC 1.11.1.7) are also implicated in lignin/suberin formation during the polymerization of monolignols synthetized in the final steps of the phenylpropanoid pathway [74].…”
Section: Genetic Basis Of Seed Dormancy Release In Legumesmentioning
confidence: 99%
“…These persistence characteristics may be altered upon exposure of mother plants to various biotic and abiotic stress conditions during seed development and prior to dispersal. Some dispersal unit characteristics underlying seed persistence in the soil are of maternal origin, embedded within the dead organs enclosing the embryos (DOEEs) including the seed coat (dry, dehiscent fruits), the pericarp (dry, indehiscent fruits) and dead floral bracts (glumes, lemmas, paleas) in grasses [33]. DOEEs are thought to function in seed dispersal and in protecting the embryo from mechanical and physical damages.…”
Section: Seed Persistence In the Soilmentioning
confidence: 99%
“…DOEEs are thought to function in seed dispersal and in protecting the embryo from mechanical and physical damages. However, detailed study of DOEEs revealed their capacity to store substances such as proteins (e.g., hydrolytic enzymes), growth factors (e.g., phytohormones) and various metabolites that might affect various aspects of seed biology including longevity, germination, and seedling vigor [33].…”
Section: Seed Persistence In the Soilmentioning
confidence: 99%
“…In addition, these dead structures can potentially protect fruits from predation, position and anchor fruits in the soil as well as absorb moisture to stimulate germination [2]. Recently, Raviv et al reviewed the biochemical activities of dead structures enclosing the fruits of several plant species belonging to different families, including Poaceae, and concluded that these structures contain various active enzymes involved in the hydrolysis process (e.g., nucleases, proteases, and chitinases) and detoxification of reactive oxygen species [3]. Such enzymes can control seed germination and enhance growth of germinated seedlings [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Raviv et al reviewed the biochemical activities of dead structures enclosing the fruits of several plant species belonging to different families, including Poaceae, and concluded that these structures contain various active enzymes involved in the hydrolysis process (e.g., nucleases, proteases, and chitinases) and detoxification of reactive oxygen species [3]. Such enzymes can control seed germination and enhance growth of germinated seedlings [3,4]. In addition, dead structures around fruits of Arabidopsis thaliana and Sinapis alba had active hydrolytic enzymes that can be released upon hydrolyses to increase the survival rate of emerged seedlings [5].…”
Section: Introductionmentioning
confidence: 99%